The Impact of the Information Security Policies on Organizational Performance - Kamal Aldin Yousif Yaseen (International Journal of Engineering and Management Research, 2023)
This study aims to explore the importance of enforcing a solid information security policy on the different institutions, giving a conceptual overview on the relationship between information security practices and organizational performance, presenting global indicators in peer-reviewed journals and records of information security firms and platforms, comparing best practices to productivity and improved performance, Analysing various risks and proposing the best solutions and appropriate protection techniques by following the best various strategies and techniques, propose the mitigation strategic prevention and hybrid techniques to protect the information due to their less expensive and simplicity.